Essential Hypertension: Cardiovascular Response to Breath Hold Combined with Exercise - Hoffmann, U.; Urban, P.; Koschate, J.; Drescher, U.; Pfister, R.; Michels, G. (International Journal of Sports Medicine, 2015)
Essential hypertension (EH) is a widespread disease and might be prevalent in apnea divers and master athletes. Little is known about the influence of EH and the antihypertensive drugs (AHD) on cardiovascular reactions to combined breath hold (BH) and exercise. In this pilot study, healthy divers (HCON) were compared with treated hypertensive divers with regard to heart rate (HR) and mean blood-pressure (MAP) responses to BH, exercise and the combination of both. Ten subjects with EH and ten healthy divers were tested. 3 different 20 s stimuli were applied: BH combined with 30 W or 150 W and 150 W without BH. The time-charts during the stress intervals and during recovery were compared. Subjects treated with an angiotensin-converting enzyme (ACE) inhibitor showed higher changes for MAP values if breath hold was performed. HR responses were obviously changed if a β-blocker was part of the medication. One subject showed extreme MAP responses to all stimuli and conspicuous HR if BH was involved. The modulation of HR-/MAP-response in EH subjects depends on the mechanisms of antihypertensive agents. The combination of an ACE inhibitor and a β-blocker may give the best protection. It is recommended to include short apnea tests in the fitness-to-dive examination to individually predict potential endangerment.
Keywords: apnea; fitness-to-dive examination; heart rate-pressure-product; antihypertensive drugs; diving response